1979
DOI: 10.1002/cber.19791120909
|View full text |Cite
|
Sign up to set email alerts
|

Eine umkehrbare Gerüstumlagerung im trans‐ Erythrinan‐Ringsystem, II. Neue trans‐ und 1(6→7)abeotrans‐ Erythrinane

Abstract: Eingegangen a m 27. Dezember 1978Der Gultigkeitsbereich der umkehrbaren Gerustumlagerung 1 2 wird abgegrenzt. Aus I und seinen monosubstituierten Derivaten 5 -9 erhalt man die trans-Diol-l(6 + 7)abeo-truns-erythrinanlactame (Diol-A*-Derivate) 10 -23, wahrend Verbindungen vom Typus 3/4 und 24/25 unter den angewandten Bedingungen nicht darstellbar sind. Unter bestimmten Bedingungen konnen die Reaktionen in beiden Richtungen auch in zwei Schritten durchgefuhrt werden. Im Umlagerungsschritt wechseln jeweils vier P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Furthermore, Mondon et al [175] have reported that acetylation of the diol (160) yielded the rearranged product (161a) which reverted to 160 on hydrolysis. Assessment of the scope of the reversible rearrangement showed that the rearrangement step consisted of a spontaneous 1,2-shift involving four reaction centers [176]. Assessment of the scope of the reversible rearrangement showed that the rearrangement step consisted of a spontaneous 1,2-shift involving four reaction centers [176].…”
Section: Erythrina Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Mondon et al [175] have reported that acetylation of the diol (160) yielded the rearranged product (161a) which reverted to 160 on hydrolysis. Assessment of the scope of the reversible rearrangement showed that the rearrangement step consisted of a spontaneous 1,2-shift involving four reaction centers [176]. Assessment of the scope of the reversible rearrangement showed that the rearrangement step consisted of a spontaneous 1,2-shift involving four reaction centers [176].…”
Section: Erythrina Alkaloidsmentioning
confidence: 99%
“…15,16-Dimethoxy-2,8-dioxo-l, 7-cycloerythrinan earlier prepared by a concerted intermolecular alkylation of the 17^-mesylate [43], has been synthesized from homoveratrylamine in 37 per cent yield [182]. The reaction of isoquinolinopyrrolinedione (174) with 1,3-di-O-substituted butadienes proceeded in a regiospecific and regioselective manner to give erythrinan derivatives (175) and (176) (Fig. The Diels-Alder reaction of Δ -pyrroline-4,5-diones with activated butadienes which proceeds in a regio-and stereo-selective manner [183] has been applied to the synthesis of ring-D-functionalized erythrinan derivatives in acceptable yields [184][185].…”
Section: Erythrina Alkaloidsmentioning
confidence: 99%